PI 3‐kinase delta enhances axonal PIP3 to support axon regeneration in the adult CNS. Issue 8 (17th June 2020) - Nieuwenhuis, Bart; Barber, Amanda C; Evans, Rachel S; Pearson, Craig S; Fuchs, Joachim; MacQueen, Amy R; van Erp, Susan; Haenzi, Barbara; Hulshof, Lianne A; Osborne, Andrew; Conceicao, Raquel; Khatib, Tasneem Z; et al.
Abstract: Peripheral nervous system (PNS) neurons support axon regeneration into adulthood, whereas central nervous system (CNS) neurons lose regenerative ability after development. To better understand this decline whilst aiming to improve regeneration, we focused on phosphoinositide 3‐kinase (PI3K) and its product phosphatidylinositol (3, 4, 5)‐trisphosphate (PIP3 ). We demonstrate that adult PNS neurons utilise two catalytic subunits of PI3K for axon regeneration: p110α and p110δ. However, in the CNS, axonal PIP3 decreases with development at the time when axon transport declines and regenerative competence is lost. Overexpressing p110α in CNS neurons had no effect; however, expression of p110δ restored axonal PIP3 and increased regenerative axon transport. p110δ expression enhanced CNS regeneration in both rat and human neurons and in transgenic mice, functioning in the same way as the hyperactivating H1047R mutation of p110α. Furthermore, viral delivery of p110δ promoted robust regeneration after optic nerve injury. These findings establish a deficit of axonal PIP3 as a key reason for intrinsic regeneration failure and demonstrate that native p110δ facilitates axon regeneration by functioning in a hyperactive fashion. Synopsis: CNS axons lose the ability to regenerate with maturity, whilst PNS axons do not. This study shows that PIP3 levels decline in CNS neurons at the time when regenerative ability is lost. CNS overexpression of one isoform of PI3K, p110δ, enhances axonal PIP3, axon transport, and regenerative ability. p110α and p110δ were found to be required for axon regeneration in adult PNS neurons, however PI3K and PIP3 declined in CNS neurons as they developed to maturity. p110α or p110δ were overexpressed in mature CNS neurons, but only p110δ restored PIP3 and regeneration, whilst the activating H1047R mutation was required in p110α to promote regeneration similarly. p110δ mediated regeneration through multiple downstream pathways, including mTOR, pS6, CRMP2, ARF6, and increased axonal transport of integrins and Rab11‐positive endosomes. Transgenic expression of p110δ or hyperactive p110α H1047R stimulated axon regeneration after optic nerve injury and increased RGC survival, whilst viral delivery of p110δ led to further enhanced axon regeneration. Abstract : CNS axons lose the ability to regenerate with maturity, whilst PNS axons do not. This study shows that PIP3 levels decline in CNS neurons at the time when regenerative ability is lost. CNS overexpression of one isoform of PI3K, p110δ, enhances axonal PIP3, axon transport, and regenerative ability.